A STRAIGHTFORWARD METHOD FOR DETERMINATION OF Ba AND Sr TOTAL CONTENT IN NATURAL ZEOLITES BASED ON MICROWAVE-ASSISTED DIGESTION AND INDUCTIVELY COUPLED PLASMA OPTICAL EMISSION SPECTROMETRY - SENILA, Marin; CADAR, Oana; SENILA, Lacrimioara; BECZE, Anca; ROMAN, Marius; ANGYUS, Bogdan; BRUJ, Gabriel (Studia Universitatis Babeș-Bolyai Chemia, 2021)
Ba and Sr may occur in relatively high content in natural zeolites and can contribute to the zeolites ion-exchange properties. In addition, some soluble compounds of Ba and Sr can be toxic, thus their determination is important. The aim of this paper was the development and validation of a method for determination of Ba and Sr in zeolites based on microwave-assisted acid digestion and inductively coupled plasma optical emission spectrometry (ICP-OES). For validation, a certified reference material (BCS-CRM 375/1) was used in the accuracy study, and the obtained recoveries were 92 ± 10 % for Ba and 95 ± 12 % for Sr. A mixture of HNO3:HCl:HF of 3:9:2 (v/v/v) and a digestion time of 40 min were found to give recoveries in the range of 80-120 %. The obtained LOQs in ICP-OES allowed the quantification of concentrations above 5.0 mg kg-1 Ba and 3.8 mg kg-1 Sr. The method was applied for the determination of Ba and Sr in five zeolite samples, and concentrations of 422 – 580 mg kg-1 for Ba and 115 – 183 mg kg-1 for Sr were found. The obtained performance parameters were in agreement with the requirements of international guidelines regarding methods validation.